Investigating the role of psychological need satisfaction as a moderator in the relationship between job demands and turnover intention among nurses. Issue 1 (6th January 2020) - Boudrias, Valérie; Trépanier, Sarah-Geneviève; Foucreault, Annie; Peterson, Clayton; Fernet, Claude
Abstract : Purpose: Job demands can contribute to nurses' turnover intention and this can have an impact on health services among the general population. It appears important to identify the work environment factors associated with turnover intention, as well as the psychological resources liable to act on this relationship. Drawing on self-determination theory (SDT), the purpose of this study ( n =1179) is to investigate the relationship between two job demands (role ambiguity and role conflict) and turnover intention, as well as the moderating role of basic need satisfaction (autonomy, competence and relatedness) within these relationships. Design/methodology/approach: This cross-sectional study was conducted among nurses (Québec, Canada). Nurses completed an online questionnaire. To test the proposed moderating effect of satisfaction of the three psychological needs (i.e. autonomy, competence and relatedness) in the relationship between job demands (i.e. role ambiguity and role conflict) and turnover intention, path analysis was conducted using Mplus v.8 (Muthén and Muthen, 2017). Two models, one for each demand, were tested. Findings: As expected, role ambiguity and role conflict are positively related to turnover intention. Results reveal a significant interaction between role ambiguity and satisfaction of the need for autonomy in the prediction of turnover intention. The satisfaction of the need for competence and the satisfaction of the need for relatedness did not moderate the relationship between role ambiguity and turnover intention. Satisfaction of the need for autonomy moderated the relationship between role conflict and turnover intention. Moreover, results revealed a significant interaction between role conflict and satisfaction of the need for competence in the prediction of turnover intention. Satisfaction of the need for relatedness did not moderate the relationship between role conflict and turnover intention. Research limitations/implications: The results align with the theoretical propositions of several leading theories in occupational health which state that workers' psychological functioning derives not only from the job characteristics of their work environment, but also from the psychological resources at their disposal. The study contributes to SDT. First, to date, this is the first study to investigate basic psychological need satisfaction as a moderator in the relationship between contextual factors and workers' functioning. Second, the findings revealed the importance of assessing psychological needs separately, as each contributes in a specific way to workers' work-related attitudes and adaptation to their professional environment. Practical implications: Perceptions of autonomy and competence act as key psychological resources for nurses. Managerial support for autonomy (e.g. providing nurses with meaningful information regarding their work) and competence (e.g. providing nurses with frequent positive feedback regarding their work efforts) constitutes a series of key management practices that can foster perceptions of autonomy and competence. The findings show that two role stressors predict nurses' turnover intention. As such, health care establishments are encouraged to focus on interventions that reduce uncertainties and conflicting situations from nurses (provide clear job descriptions and effective communication). Social implications: By promoting a sense of effectiveness and feelings of self-endorsement at work, health care establishments can reduce nurses' turnover intention and help prevent staffing shortages among this important work group. Originality/value: Although past research shows that workers' motivational profile can modulate the relationship between characteristics within the work environment and workers' functioning, studying the quality of work motivation is not sufficient to completely understand the factors that can influence workers' reactions to job demands. Need satisfaction is crucial to the development and maintenance of high quality motivation. Evaluating need satisfaction as a moderator in the stressor–strain relationship could offer a better understanding of the psychological experiences that can promote workers' adaptation to their work environment. To date, no study has investigated the buffering role of psychological needs in the stressor–strain relationship.